Reverse load flow analysis - Asif, Md. Iqbal Hossain; Azim, Md. Sobhanul; Mahbub, Salwa (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.